Evidence for wave heating in the solar corona. (15th May 2013) - Hahn, Michael
Abstract : The temperature of the Sun increases over a short distance from a few thousand degrees in the photosphere to over a million degrees in the corona. To understand coronal heating is one of the major problems in astrophysics. There is general agreement that the energy source is convective motion in and below the photosphere. It remains to determine how this mechanical energy is transported outward into the corona and then deposited as heat. Two classes of models have been proposed, namely those that rely on magnetic reconnection and those that rely on waves, particularly Alfvén waves. There is increasing evidence that waves are ubiquitous in the corona. However, a difficulty for wave‐driven models has been that most theories predict Alfvén waves to be undamped in the corona, and therefore they cannot dissipate their energy into heat. Our research has shown unambiguous observational evidence that the waves do damp at sufficiently low heights in the corona to be important for coronal heating.